The Dynamics of Student Protests: Analyzing Public Sentiment and Policy Implications of Indonesia’s VAT Increase in 2025 - Dwi Savandha, Septien; Azzahra, Adelia (Cakrawala Repositori IMWI, 2025)
In March 2025, Indonesia witnessed nationwide student-led protests against fiscal austerity measures, including a VAT hike and military reforms. These demonstrations, organized under the #IndonesiaGelap movement, reflected deepening public discontent over economic inequality and democratic backsliding. This study examines the root causes of the protests, maps public sentiment through digital and ethnographic data, and assesses their implications for Indonesia’s governance framework. A qualitative approach combining social media analysis (2,000 posts) and semi-structured interviews with 15 protest organizers was employed, using thematic decomposition and sentiment analysis. The protests were driven by the VAT increase’s regressive impact (cited by 78% of participants) and amendments to the TNI Law, which enabled military encroachment into civilian roles (62% of social media criticism). Sentiment analysis revealed 65% negative discourse, emphasizing terms such as “oppressive” and “unfair,” while 22% expressed solidarity with the protesters. Demands focused on tax justice, military depoliticization, and agrarian reforms, though government responses prioritized fiscal stability over equity. The movement’s digital strategies, including encrypted apps and viral anthems, bridged urban-rural divides but faced algorithmic censorship. In conclusion, the 2025 protests underscore systemic tensions between fiscal reforms and democratic accountability, highlighting the need for policies that address youth disillusionment and rural marginalization.